Growth initial Conilon Coffee Under water defiCit in soil - Rodrigues, Rogério Rangel; Pizetta, Samuel Cola; Silva, Nicolly Kalliliny Cavalcanti; Ribeiro, Wilian Rodrigues; dos Reis, Edvaldo Fialho (Coffee Science - ISSN 1984-3909, 2016)
The growth conilon coffee (Coffea canephora Pierre ex A. Froehner) can be influenced significantly by reducing the available water in the soil, especially during its early development. Thus, the objective was to evaluate the influence of soil water deficit on the initial development of the conilon coffee Robusta Tropical cultivar in different water availability. The experiment was carried out in a greenhouse of Agricultural Sciences Center of the Federal University of Espírito Santo, in Alegre, ES, consisting of four treatments (100, 50, 30 and 10% of available soil water) in a completely randomized design with four replicates. After one hundred and twenty days, the variables were: rate of growth in biomass, growth rate in height, growth rate in leaf area and stem growth rate. The results showed that the growth rate on biomass growing and stem height at conilon coffee decreased linearly with the reduction of available water in the soil. The highest growth rate in leaf area were obtained in 84.76 % of the water available in the soil.